A Novel Method to Design Delay-Scheduled Controllers for Damping Inter-Area Oscillations - Asghari, Rasoul; Mozafari, Babak; Naderi, Mohammad Salay; Amraee, Turaj; Nurmanova, Venera; Bagheri, Mehdi (IEEE, 2018)
The main problem of time delay in the application of remote signals is that it limits the contribution of the controller devices in damping inter-area oscillations, and thus to overcome this problem, we proposed a new time delayed controller in this paper. The controller takes the advantage of delay as a design parameter to solve the SVC contribution limitation problem resulting from delays in feedback loops. To determine the delay and controller parameters, an algorithm is proposed to minimize the rightmost real part of the electromechanical oscillation modes in the design stage such that the system robustness against the small variations of time delay is provided. The feasibility of the proposed method is evaluated by conducting a number of simulations on the standard four-machine and 16-machine 68-bus test power systems. The results reveal that compared to the existing methods, the proposed method not only exhibits a better damaging performance but also introduces a significant delay margin in a certain range of feedback delays.
https://ieeexplore.ieee.org/stamp/stamp.jsp?tp=&arnumber=8509578
Keywords: spectral abscissa; large-scale power systems; delay differential-algebraic equations; delay range stability; oscillators; power system stability; Research Subject Categories::TECHNOLOGY